POTENCY OF VINEGAR THERAPY IN OTOMYCOSIS PATIENTS - Sulaiman, Eman; Purwanto, Bambang; Lasminingrum, Lina; Dewi, Yussy Afriani; Mahdiani, Sally (Journal of Medicine and Health, 2015)
Otomycosis is an outer ear canal infection caused by fungi. Clinicians are trying to find out the most effective antifungal drug for treating otomycosis. Traditionally Apple cider vinegar has been used for the treatment of various diseases, including antifungal.The high cost in otomycosis treatment effort, long duration of treatment, high recurrence rate, and the difficulty in the application of drugs in the otomycosis treatment have encouraged the researcher to do this study. Having evaluated the improvement of clinical symptoms, otoscopy view and examination of KOH 10% in patients receiving apple cider vinegar therap, this study uses descriptive study design of four otomycosis patients in the ORL HNS outpatient clinic of Hasan Sadikin Hospital Bandung from July to August 2014. Having evaluated a clinical symptoms improvement, it is found out that there is an increase of otoscopy view and examination of KOH 10% in patients receiving apple cider vinegar. In other words, there is an Improvement of clinical symptoms, otoscopy view, and examination of KOH 10% in patients receiving apple cider vinegar therapy. Topical apple cider vinegar therapy gives a good result in the improvement of clinical symptom,otoscopy view, and examination of KOH 10% in otomycosis patients. Keywords: otomikosis, sign and symptoms improvement, apple cider vinegar.